Analisis Kebutuhan Bahasa Inggris Pramusaji di Hotel Berbintang 5 di Bali - Wulandari, Ni Luh Manda; Rahmawati, Putu Indah (Universitas Pendidikan Ganesha, 2020)
This study aimed at analyzing the English language skills functions and expressions needed as a waiter/ss. This research was a qualitative descriptive. The method used in obtaining the required information were interviews and documentation, in which subjects in this research were Asst. F&B Service Manager, Restaurant Manager, Supervisor, and Restaurant Staff in 5-Star Hotel in Bali. The results of this study indicated that (1) Speaking & listening skills are the main poins that must be mastered by a waiter/ss, and the accuracy of grammar and fluency in communication also have an equally important role, (2) The expression of the language used adjusts to predetermined language functions based on the implementation of Sequence of Service (SOS) in restaurants. From the results of this study it may be necessary to further research on analyzing the needs of English Waiters in a broader scope.